2015
DOI: 10.4238/2015.january.23.11
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the RORα gene in Inner Mongolian cashmere goat hair follicles

Abstract: ABSTRACT. The expression of retinoid-acid-related orphan receptor α (RORα) was evaluated at the mRNA level using real-time polymerase chain reaction (qRT-PCR), and its expression localization was determined by in situ hybridization of adult Inner Mongolian cashmere goats at different times of the year. In situ hybridization demonstrated that RORα was expressed in secondary hair follicles of the hair shaft, inner root sheath, outer root sheath, medulla, and other parts that are target organs of the RORα recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hematologic parameters are important indicators reflecting the immune status and health of the human or animal organism and are used as biomarkers in GWASs [17]. In recent years, GWASs have been used in human studies to locate more than 60 quantitative trait loci (QTLs) for blood traits among people of European ancestry, the Japanese and African Americans [18,19,20,21,22,23,24,25]. In the field of animal husbandry, pigs have been bred for disease resistance earlier than other species.…”
Section: Introductionmentioning
confidence: 99%
“…Hematologic parameters are important indicators reflecting the immune status and health of the human or animal organism and are used as biomarkers in GWASs [17]. In recent years, GWASs have been used in human studies to locate more than 60 quantitative trait loci (QTLs) for blood traits among people of European ancestry, the Japanese and African Americans [18,19,20,21,22,23,24,25]. In the field of animal husbandry, pigs have been bred for disease resistance earlier than other species.…”
Section: Introductionmentioning
confidence: 99%
“…At present, although it has been reported that Mel1a protein is expressed in the inner root sheath of skin feather follicles, the research on it has mainly focused on ovaries and follicles He et al, 2014;Sundaresan et al, 2009;Lee et al, 2001). Zhao et al, (2015) found that ROR was expressed in the hair stem, inner root sheath, outer root sheath and medulla of cashmere goats. However, during the anagen period, as the skin feather follicles continue to develop and mature, the overall expression site of ROR has not change too much.…”
Section: Immunolocalization Of Mel1a and Ror Proteins In Skin Feathe...mentioning
confidence: 99%
“…Studies have shown that Mel1a receptors may be related to the circadian rhythm of organisms and it is speculated that melatonin may play an important role in the biological function of circadian secretion through Mel1a receptors (Zawilska et al, 2009). And the expression of ROR protein has a positive effect on the growth of villi (Zhao et al, 2015).…”
Section: Immunolocalization Of Mel1a and Ror Proteins In Skin Feathe...mentioning
confidence: 99%